2011
DOI: 10.5402/2011/962186
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Parathyroid Disease during Thyroid Surgery: Should We Remove Them?

Abstract: Aim. Despite an incidence of parathyroid “incidentalomas” of 0.2%–4.5%, only approximately 135 cases have been reported in the literature. We present eight patients in whom an incidental abnormal parathyroid gland was found during routine thyroid surgery. We have reviewed the literature and postulate whether these glands could represent further evidence of a preclinical stage of primary hyperparathyroidism. Methods. A retrospective analysis of all 236 thyroid operations performed by a single surgeon was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Our findings demonstrate that MGD was diagnosed in 219 patients, constituting 6% out of all patients being operated on for benign and malignant thyroid lesions at our institution. Furthermore, our study shows that incidental identification of enlarged parathyroid glands is a relatively frequent discovery during thyroid surgery, which is in agreement with other studies demonstrating MGD in 0.2-4.5% of patients (3)(4)(5)(6)(7)(8). It is worth mentioning that Boehm et al suggested radiation exposure to play a certain role as a possible risk factor for the development of hyperparathyroidism as a late adverse effect after the accident at Chernobyl nuclear plant in 1986 (16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings demonstrate that MGD was diagnosed in 219 patients, constituting 6% out of all patients being operated on for benign and malignant thyroid lesions at our institution. Furthermore, our study shows that incidental identification of enlarged parathyroid glands is a relatively frequent discovery during thyroid surgery, which is in agreement with other studies demonstrating MGD in 0.2-4.5% of patients (3)(4)(5)(6)(7)(8). It is worth mentioning that Boehm et al suggested radiation exposure to play a certain role as a possible risk factor for the development of hyperparathyroidism as a late adverse effect after the accident at Chernobyl nuclear plant in 1986 (16).…”
Section: Discussionsupporting
confidence: 92%
“…PHPT could be also associated with the multiglandular disease (MGD), which is diagnosed in patients with 2 and more enlarged parathyroid glands. According to data from published series, MGD could be diagnosed as incidental discovery during thyroid surgery in up to 34% of patients to be operated on for benign and malignant thyroid lesions (3)(4)(5)(6)(7)(8)(9). Pathogenesis of MGD and other parathyroid diseases demonstrates various molecular abnormalities, playing role for diagnosis of multiple endocrine neoplasia (MEN) and other hereditary syndromes associated with parathyroid gland lesions (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…As intraoperative parathyroid hormone (ioPTH) levels are being used to obtain a baseline at the time of a total thyroidectomy and/or at the conclusion of surgery to better direct the management of potential postoperative hypoparathyroidism, an abnormally and unexpectedly high ioPTH level will raise the question of an incidental parathyroid adenoma. Incidental parathyroid adenomas that are diagnosed at the time of thyroid surgery are reported to occur in 0.2%‐4.5% of cases . Obtaining a parathyroid hormone (PTH) level or a serum calcium level should be considered prior to surgery as a useful screening lab to reduce the unexpected incidentaloma finding or need to reoperate on a patient who may have concomitant disease.…”
Section: Resultsmentioning
confidence: 99%
“…Incidental parathyroid adenomas that are diagnosed at the time of thyroid surgery are reported to occur in 0.2%-4.5% of cases. 49 Obtaining a parathyroid hormone (PTH) level or a serum calcium level should be considered prior to surgery as a useful screening lab to reduce the unexpected incidentaloma finding or need to reoperate on a patient who may have concomitant disease. Guidelines for appropriate management of incidentally identified parathyroid adenomas should be closely followed.…”
Section: Preoperative Managementmentioning
confidence: 99%
“…Re-do surgery carries its own complications like higher chance of bleeding, damage to recurrent laryngeal nerve (<1 % in primary surgery and up to 10 % in re-do surgery) [30], post-operative hypocalcaemia due to inadverdent injury to normal parathyroid tissue either at original surgery or re-do operation [34].…”
Section: Complicationsmentioning
confidence: 99%